A methodical approach for developing high hurdlers - Wahab, K. A. (2014)
This presentation includes the annual training plan for Colorado State University`s high hurdlers, and basic explanations of targeted performance criteria, as well as the Ram`s methodical approach in developing high hurdlers. The technical and physiological objectives of the training plan comply with the basic understanding of general biomechanics and sports physiology concepts held by the vast coaching community. The following philosophy and methodology were implemented in developing 2012, NCAA D-1 Second Team All-American student athlete, Trevor Brown, who lowered his PR in the 110m hurdles from 14.21 to 13.75 between his freshman and sophomore year, and moved up to be 8th in the NCAA D-1 110h finals in 2013 with a season best of 13.55(w) receiving a first team All American Honors. Trevor`s improvements in the 60 hurdles indoors were as follows: 8.30 in 2010 senior in High School over 42" hurdles, 7.91 freshmen in CSU, 7.86 sophomore and 7.77 Junior in 2013. Trevor currently holds CSU and the Mountain West Conference records in the 110 and 60 m hurdles. Go Rams!!!